Experiencing designs and designing experiences: Emotions and theme parks from a symbolic interactionist perspective. (June 2020) - Cabanas, Edgar
Abstract: This paper aims to open a theoretical debate on the relationships between spatial design and emotional experiences in theme parks from a symbolic interactionist perspective. Whereas the interplay between emotions and space is fundamental to understanding the production and consumption of experiences at theme parks, this relationship has been insufficiently explored in theme park literature. The paper applies symbolic interactionism to comment on relevant topics in theme park literature such as atmosphere design, experience control, and visitors' engagement. In contrast to reductionistic and deterministic accounts of emotions, the paper emphasizes the indirect influence of atmospheres in visitors' emotional responses, underscores the active role that guests play in the co-production of their own experiences, and stresses the significance of role-playing to understanding visitors' engagement and immersion in the fantasies that theme parks manufacture for them. The paper also highlights the theoretical and empirical value of emotional narratives to better capture the mixed, complex, and situated experiences that visitors undergo with respect to spatial designs at theme parks. Highlights: Discusses the role that emotions play in the consumption of theme park experiences. Highlights the value of narratives to capture situated emotional responses. Underscores the active role of guests in the co-production of experience. Suggests conceptual and methodological implications for theme park analysts.